1048. Weight Gain after Initiation of Anti-Retroviral Therapy in Acute HIV-1. (31st December 2020) - Kaur, Harmanpreet; Utay, Netanya S; Lake, Jordan; Arduino, Roberto; Hongyu, Miao
Abstract: Background: Background: Excess weight gain with integrase strand transfer inhibitors (INSTIs) has been reported in some people with chronic HIV. In antiretroviral therapy (ART)-naïve people, greater weight gain over 18 months was reported with dolutegravir than other agents. We hypothesized that initiating an INSTI-based regimen during acute HIV infection (AHI) would result in more weight gain than a non-INSTI-based regimen, and INSTIs other than elvitegravir (EVG) would be associated with greater weight gain than EVG. Methods: Methods: We performed a retrospective, observational, single center chart review analysis of adults with AHI (Feibig Stages 1-5) who were initiated on ART and followed for 48 (+/- 12) weeks. Changes in weight between people on INSTI- vs non-INSTI regimens were compared, and in a subgroup analysis, EVG vs non-EVG and tenofovir alafenamide (TAF) vs non-TAF were compared. Chi-square, t-test, or Wilcoxon Rank Sum test were used, when appropriate. Results: Results: Baseline characteristics of the 61 participants are shown in Table 1. Overall median (IQR) weight change was 4.53 (1.22-8.36; within-group P< 0.0001) kg (Figure 1). Median weight change in 58 people initiated on INSTI was 4.66 (1.22-8.43; P< 0.0001) kg vs 1.64 (-3.08-6.57; P=0.75) kg in 3 people not on INSTI (between-group P= 0.33). Median weight change on EVG was 4.40 (0.91-6.71; P< 0.0001) kg vs 7.10 (4.97-13.15; P= 0.0001) kg for non-EVG INSTIs (between-group P= 0.008, Figure 2). Median weight change on TAF (n=33) was 2.66 (0.81-7.53; P= 0.002) kg vs 5.31 (3.72-9.34; P < 0.0001) kg in non-TAF (n=25) recipients (between-group P= 0.06). Lower baseline CD4 + T cell count correlated with greater weight gain (P= 0.012). No association between weight gain and race (P= 0.930) or gender (P= 0.379) was noted. Baseline characteristics and median weight change (kg) from baseline Weight change in elvitegravir vs non-elvitegravir integrase inhibitor regimen. Overall weight gain seen over 48 weeks after initiation of antiretroviral therapy calculated using the Wilcoxon Rank Sum test. Conclusion: People initiating ART during AHI gained weight over 48 weeks, with persons taking INSTIs gaining more weight, though this finding did not reach statistical significance due to small sample size. Amongst INSTI-treated persons, those not on EVG gained more weight than those on EVG. While the benefits of starting ART during AHI on immune system preservation and reservoir should not be underscored, risk and consequences of weight gain following ART initiation should be discussed when initiating ART during AHI. Disclosures: Jordan Lake, MD, Gilead Sciences (Grant/Research Support, Scientific Research Study Investigator)